Characterization of a thermal aerosol generator for HVAC filtration experiments (RP-1734). (2nd July 2020) - Wu, Tianren; Boor, Brandon E.
Abstract : HVAC filters are exposed to a diverse mixture of aerosols during their service life. Aerosol physiochemical properties can have a significant impact on the removal efficiency and loading behavior of a filter. New aerosol generation techniques are needed to age HVAC filters with particle size distributions (PSDs) representative of those found in outdoor (urban) and indoor environments. This study evaluated the physical characteristics of salt aerosol produced by a newly designed commercially available thermal aerosol generator. The thermal aerosol generator produced a high mass output of sub-micron (≤ 1, 000 nm) sodium chloride (NaCl) and potassium chloride (KCl) particles by burning a salt stick in an oxygen-propane flame. The shape of the number and mass PSDs is similar to those found in outdoor (urban) and indoor air and can be modulated by varying the rate at which the salt stick is fed into the flame. The morphology of the NaCl and KCl particles varied with size, with compact spherical or cubic structures observed below 100 nm and agglomerates observed above 100 nm. The thermal aerosol generator is a cost-effective technique for rapid ageing of HVAC filters with a PSD that more accurately represents, compared to conventional loading dusts, what filters encounter in real HVAC installations.